Estimation of glycemic index of single and multiple blend nutraceutical biscuits - Sharma, Daisy; Das, Mamoni; Barooah, Mridula; Baruah, Chandana Choudhary (Journal of Postharvest Technology, 2021)
The present study was undertaken for developing biscuits using functional ingredient like foxtail millet flour, flaxseed flour, rice bran oil and carrot flour  and to assess its Glycemic Index (GI). The GI of the biscuits was estimated through animal experimentation. The animals were divided into two groups,  one group was given 0.15 mg of standard glucose and the other group was fed with equi-load of carbohydrate content present in the developed biscuit.  The GI of the developed biscuit was calculated from the area under blood glucose response curve of the test food and reference food. The GI of the  developed biscuit was below 47 indicating that the biscuits were low glycemic. It can therefore be concluded that the developed low glycemic index  biscuits from foxtail millet, flaxseed and carrot were nutritionally rich with enhanced sensory attributes. Its hypoglycemic effect could provide potential  health benefits from degenerative diseases like diabetes mellitus..
Keywords: Glycemic index; multigrain; nutraceutical potential; biscuit; health benefit